Web-Based Sales and Inventory Information System for Enna Coffee MSME Using an Iterative Approach - Putrienna Maduma Nababan; Novriadi Antonius Siagian; Zakarias Situmorang; Desinta Purba (Login : Jurnal Teknologi Komputer, 2026)
Enna Coffee MSME still records sales and inventory manually, resulting in frequent data inaccuracies, difficulty tracking transactions, and delays in preparing sales reports. This condition also hinders the provision of integrated data for industry reporting needs to the National Industrial Information System (SIINas). This study aims to design and build a Web-Based Sales and Inventory Information System at Enna Coffee MSME to support more effective sales and inventory data management. The development method used is an iterative method that includes the stages of needs analysis, design, implementation, testing, and evaluation that are carried out repeatedly until the system meets user needs. Data collection was carried out through observation, interviews, and document studies, while data analysis used qualitative descriptive methods. The results of the study indicate that the system was successfully built according to the operational needs of Enna Coffee MSME. The system is able to assist the process of managing sales and inventory data in a structured manner, reduce the risk of recording errors, and produce sales reports and raw material reports that can be used as a source of business information and the basis for compiling industry reporting data to SIINas. Based on the research results, the developed system successfully supports the management of sales and inventory data at Enna Coffee MSMEs in a more structured manner, reduces the risk of recording errors, and provides the information needed to support business operations and industry reporting.